Challenges of learning remote reading skills for students with reading difficulties from the point of view of the teachers of the stage in the schools of the Marca District in the shadow of the Corona pandemic - Ghabash, Rania Salim Abdel-Qader (Journal of Curriculum and Teaching Methodology, 2022)
The study aimed at the challenges of learning the reading skills of students with difficulties, and the new printing from the point of view of the stage teachers in the schools of Marka District in light of the Corona pandemic. (96) a teacher and a teacher. The results of the study showed a weak view of teachers towards the possibility of learning reading skills from a distance among students with reading difficulties. The teachers also differed about the possibility of evaluating students’ reading performance from a distance, while they indicated that there are high challenges facing learning reading skills among students with reading difficulties. remote reading. In light of the previous results, the recommendations of the study were identified.